Efficacy, pharmacokinetics and safety of liposomal synthetic cannabidiol injected subcutaneously in dogs: a randomized, blinded, placebo-controlled, crossover clinical trial - Shilo-Benjamini, Yael; Milgram, Joshua; Lavy, Eran; Quint, Maxim; Barasch, Dinorah; Cern, Ahuva; Barenholz, Yechezkel (Frontiers in Veterinary Science, 2026)
BackgroundCannabidiol (CBD) has anti-nociceptive and anti-inflammatory characteristics, and was reported to provide analgesia in dogs with osteoarthritis. However, oral CBD has poor bioavailability due to significant first-pass hepatic metabolism. Encapsulation of CBD into liposomes was reported by our group to facilitate CBD slow-release, and provide high bioavailability and analgesia in a pilot study in dogs with osteoarthritis.ObjectivesTo determine the pharmacokinetics and effects of liposomal-synthetic-cannabidiol (L-sCBD) injection compared with placebo in dogs with radiographically confirmed naturally-occurring osteoarthritis.AnimalsEight client-owned dogs (4 males, 4 females; 8.5 [4.5–12.5] years-old; 34.9 [22.7–42.7] kg).MethodsDogs were injected subcutaneously twice with a 4-week interval; once with 7 mg/kg L-sCBD (50 mg/mL) and once with empty liposomes of identical lipid composition (placebo; equivalent volume) in a randomized, blinded, crossover design. Each dog routine analgesics (e.g., non-steroidal anti-inflammatories) were continued. Blood was sampled for CBD and metabolites concentrations, complete blood count and serum chemistry up to 4-weeks post-injections. Efficacy was assessed via activity monitoring collar and scorings by owners and two veterinary specialists. Vital signs and local response were monitored. Data analysis used aligned rank transform ANOVA, permutation test and Wilcoxon signed-rank test (p-value < 0.05).ResultsCBD plasma concentrations were detected up to 4-weeks; median peak plasma concentration (Cmax) was 58.2 [range 35.1–141.0] ng/mL, median time to Cmax was 3 [3–7] days and median half-life 6.1 [4.6–9.5] days. The metabolites 6/7-hydroxy-CBD, and 7-carboxy-CBD were detected at low concentrations. Pain and lameness scores and behavior were significantly improved after L-sCBD treatment versus placebo. At 3-days after L-sCBD treatment, neutrophils and alkaline-phosphatase increased significantly, while hematocrit and albumin decreased (all within reference range, except neutrophils in 2/8 dogs). Adverse effects included 2-days fever and a minor-moderate local swelling, which resolved spontaneously.Conclusions and clinical relevanceSubcutaneous L-sCBD provided long-term CBD plasma concentrations, improved analgesia and was tolerated by all dogs. A larger clinical cohort is required to further assess L-sCBD benefits and safety.